2004
DOI: 10.1002/ijc.20744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of c‐Jun as a critical mediator for the intracrine 24 kDa FGF‐2 isoform‐induced cell proliferation

Abstract: Tumor cells frequently synthesize an N-terminally extended the FGF-2 isoform of 24 kDa devoid of signal peptide but that contains a functional nuclear localization sequence (NLS). Although the signaling pathways elicited by secreted FGF-2 are well described, the molecular mechanisms involved in the growth promoting action of nuclearized 24 kDa FGF-2 remain unknown. The cancer cell line AR4-2J was engineered to stably express only the 24 kDa FGF-2 isoform and cDNA microarrays were used to identify targets impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The FGF2 LMW and HMW isoforms have been reported to evoke different biological functions in a variety of cell types [2,12,28]. Transfection of FGF2 isoforms in an osteoblastic cell line showed that neutralizing FGF2 antibodies blocked cell growth in FGF2 LMW overexpressing cells but not in FGF2 HMW isoforms overexpressing cells, suggesting that the FGF2 HMW isoforms modulate cell growth and DNA synthesis by a mechanism independent of its cell surface receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…The FGF2 LMW and HMW isoforms have been reported to evoke different biological functions in a variety of cell types [2,12,28]. Transfection of FGF2 isoforms in an osteoblastic cell line showed that neutralizing FGF2 antibodies blocked cell growth in FGF2 LMW overexpressing cells but not in FGF2 HMW isoforms overexpressing cells, suggesting that the FGF2 HMW isoforms modulate cell growth and DNA synthesis by a mechanism independent of its cell surface receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Distinct 18 kDa and 24 kDa FGF-2 isoforms, synthesized from a single mRNA through the use of alternative initiation codons, mediate autocrine/ paracrine and intracrine signaling, respectively (36). Nuclear FGF-2 has been associated with increased tumor cell survival and enhanced metastatic capability in vivo (38), direct regulation of transcription (39) and mRNA splicing (40), and activation of Erk-MAPK signaling, leading to expression of the cell cycle regulator c-Jun (41). The EGFlike growth factors TGF-a and amphiregulin have been reported to reside in nuclei in several cell types, but a specialized role for these nuclear isoforms is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…1D), and Egr-1 (Fig. 1G), which are known to be related to cell proliferation (1,6,16,22,23,34,46). Camostat feeding rapidly upregulated the expression of 17 of 18 early response genes at the mRNA level by 2.4-to 600-fold (Table 1).…”
Section: Induction Of Early Response Gene Expression Shortly After Camentioning
confidence: 97%